Epidemiology of overweight and obesity in school going children: 11-15 years in the urban area of Cuttack city - Kanyari, S. Suneeti; Satapathy, Durga M.; Giri, Rama C. (International Journal of Research in Medical Sciences, 2019)
Background: The world health organization has described obesity as one of today’s most neglected public health problems, affecting developed and developing countries in the world. A dramatic increase in overweight and obesity among children and adolescent has raised the concern of various public health physicians especially in developing country like India. This study was conducted with an objective to study the prevalence of overweight and obesity and its associated risk factors among school going children of Cuttack city. Methods: School based cross sectional study was done among the children of 6th to 10th class. To calculate the maximum sample size prevalence of obesity was assumed to be 10%, taking absolute error of 2% and 10% non-response rate the sample was calculated to be 1000. By multistage sampling method the children were selected. Data was collected using a pre-designed and pre-tested questionnaire and analyzed by using SPSS version 16. Results: The combined prevalence of overweight and obesity was 20.2% and it was higher among boys (20.6%) than girls (19.8%). Overweight and obesity was found to be significantly associated with type of school, parent’s occupation, hours of using TV/computer, eating habit, family history of obesity, type of family and mode of transport to school. Conclusions: Prevalence of overweight and obesity was found to be high in school going children, which indicates an urgent need to increase awareness via education and motivation of all stakeholders to prevent the complications in future.